Odpowiedzi

2010-03-29T19:20:24+02:00
A)-3x=2x-10
-5x=-10/÷(-5)
x=2
b)2x-2=7-x
3x=9 /÷3
x=3
c)10=4-2x
2x=-6 /÷2
x=-3
d)-(2x-1)=4
-2x+1=4
-2x=3 /÷(-2)
x=-1,5
e)2(x+1)=x
2x-2=x
x=2
f)2t-(3t+1)=6
2t-3t-1=6
-t=7 /÷(-1)
t=-7
  • Użytkownik Zadane
2010-03-29T19:24:35+02:00
A)-3x-2x=-10
-5x=-10 |:(-5)
x=2
b)2x+x=7+2
3x=9|:3
x=3
c)10=4-2x
10-4=2x
6=2x|:2
x=3
d)-2x-2=x
-2x-x=2
-3x=2|:(-3)
x=2/3 (dwie trzecie)
e) 2x+2=x
x=-2
f) 2t-3t-1=6
-t=6+1|:(-1)
t=7
  • Użytkownik Zadane
2010-03-29T19:26:34+02:00
A)-3x-2x=10
-5x=10 /:-5
x=-2

b)2x-2=7-x
2x+x=7+2
3x=9 /:3
x=3

c)10=4-2x
-2x=4-10
-2x=-6 /:-2
x=3

d)-(2x-1)=4
-2x+1=4
-2x=4-1 /:-2
x=-2:3 kreska ulamkowa

e)2(x+1)=x
2x+2=x
2x-x=-2
x=-2

f)2t-(3t+1)=6
2t-3t=6+1
-1t=7 /:-1
t=-7